Experience of Continuity of Care Mitigates Poorer Infant Temperament for Women Reporting Elevated Hardship During Pregnancy: Birth In The Time of COVID (BITTOC) Study - McLean, Mia; Lequertier, Belinda; King, Suzanne; Kildea, Sue; Keedle, Hazel; Dahlen, Hannah G (Elsevier BV, 2026)
Problem: It is unknown whether unborn infants exposed to their mothers’ uncontrollable stressful life events could benefit from the continuity of their mothers’ prenatal carer. Background: Maternal stress in pregnancy predicts poorer child outcomes. Continuity of care improves maternal mental health. Aim: Determine whether continuity of care moderates association between prenatal maternal stress due to COVID-19 and infant negative emotionality at age 6 months. Methods: Australian women, pregnant during the pandemic, completed a survey detailing their level of continuity of maternity care, pandemic-related difficulties (objective hardship), cognitive appraisal of, and subjective distress related to, COVID-19. Six months post-birth, they reported on their mental health, COVID-19 related stress and their infants’ negative emotionality (n = 903). Findings: Hierarchical multiple regression analysis showed that higher prenatal pandemic-related subjective distress was associated with greater infant negative emotionality. Interaction analyses determined that, for women exposed to higher levels of objective hardship in pregnancy, the more they experienced continuity of carer, the lower their child's negative emotionality at age 6 months. This relationship was not evident for dyads exposed to lower objective hardship. However, actual model of maternity care did not moderate the relationships between COVID-19-related prenatal maternal stress and infant negative emotionality. All models accounted for 6-month maternal COVID-19 objective hardship and subjective stress as well as depressive symptoms. Discussion: We found that the protective effect of experienced continuity of care, small but potentially consequential, was most evident among women exposed to high COVID-19-related hardship. This finding supports the roll-out of maternity care models that foster relational continuity for at-risk pregnant women with additional medical and psychological needs. Conclusion: For women most exposed to uncontrollable stressful events, such as pandemic-related restrictions and threat, their experience of high continuity of care may predict long-term benefits for their infant's temperament.
Keywords: Continuity of care, Temperament; Covid-19 pandemic; Infancy; Midwifery; Pregnancy; Stress; 3215 Reproductive Medicine; 4204 Midwifery; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Behavioral and Social Science; Maternal Health; Prevention; Mental Health; Pediatric Research Initiative; Infectious Diseases; Coronaviruses; Clinical Research; Women's Health; Basic Behavioral and Social Science; Perinatal Period - Conditions Originating in Perinatal Period; Coronaviruses Disparities and At-Risk Populations; Emerging Infectious Diseases; Pregnancy; Conditions Affecting the Embryonic and Fetal Periods; Reproductive health and childbirth; 3 Good Health and Well Being; 1110 Nursing; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services; Humans; Female; Pregnancy; COVID-19; Adult; Australia; Continuity of Patient Care; Infant; Stress, Psychological; Temperament; Pregnant People; Surveys and Questionnaires; Mothers; SARS-CoV-2; Prenatal Care; Humans; Prenatal Care; Stress, Psychological; Temperament; Mothers; Pregnancy; Adult; Infant; Continuity of Patient Care; Australia; Female; Surveys and Questionnaires; COVID-19; SARS-CoV-2; Pregnant People